2015
DOI: 10.31729/jnma.2789
|View full text |Cite
|
Sign up to set email alerts
|

Visualisation of Rouviere’s Sulcus during Laparoscopic Cholecystectomy

Abstract: Introduction: Safe dissection of Calot’s Triangle is important during the performance of laparascopic cholucystectomy. The purpose of the study is to determine the frequency of demonstrable Rouviere’s sulcus in patients with symptomatic gall stones and its role in safe dissection in Calot’s triangle. Methods: This is a prospective descriptive study design done in Department of surgery, Kathmandu Medical College Teaching Hospital from Jan 2013 to Jan 2015. Patients who were posted for laparoscopic cholecy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…The current study matches the abovementioned range. Thapa et al 16 reported visualized Rouviere's sulcus in of 75% of patients, Dahmane et al 8 reported an incidence of 82%, while Peti et al 7 described an incidence of 80%. The highest reported incidence of Rouviere's sulcus (> 90% visualization rate) was reported by Singh et al 12 and Kumar et al 17 In a recent meta-analysis of 23 anatomical or laparoscopic studies, Cheruiyot et al 18 reported an overall incidence of 83%.…”
Section: Discussionmentioning
confidence: 99%
“…The current study matches the abovementioned range. Thapa et al 16 reported visualized Rouviere's sulcus in of 75% of patients, Dahmane et al 8 reported an incidence of 82%, while Peti et al 7 described an incidence of 80%. The highest reported incidence of Rouviere's sulcus (> 90% visualization rate) was reported by Singh et al 12 and Kumar et al 17 In a recent meta-analysis of 23 anatomical or laparoscopic studies, Cheruiyot et al 18 reported an overall incidence of 83%.…”
Section: Discussionmentioning
confidence: 99%
“…The Rouviere's sulcus (RS) thus can be used as a safe anatomical landmark that is present on the hilar surface of liver [ 13 ]. So, it is pertinent to know more about the anatomical details and its frequency in the population [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the RS was present in 169 (93.9%) and absent in 11 (6.1%) of the patients undergoing LC. Earlier studies have shown that RS is usually seen in majority of population during LC compared to open surgery [ [10] , [11] , [12] , [13] , [14] ]. Dahmane et al [ 13 ] who reported that Rouviere's sulcus was present in 82% of normal livers, and open RS was the commonest among them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anterior callus opening was performed in 69 cases (69%) and in at least 31 cases (31%). These are Tapa et al 14 cases of early Rovier's disease were found in 75% of the patients, Mohamed et al 15 Fifteen of them described Rover depression in 73% of the cases.…”
Section: Table 1: Baseline Characteristics Of the Study Participantsmentioning
confidence: 98%